The Development of a Character Education Model Based on Maluku Folklore for Early Childhood - Emma Rumahlewang; Rosmarin Tutupary; Ferdinanda Sherly Noya; Rahma Amorsea; Vani Bugis (PT. Global Research Collaboration, 2026)
Culturally grounded learning. Unlike previous studies, which mainly used folktales from Java and other regions of Indonesia, this research introduces a novel contribution by developing and empirically testing a Maluku folktale-based model in early childhood education (ECE) settings in the Nusaniwe District. The study aims to produce a valid, practical, and effective character education model using the Research and Development (R&D) approach adapted from Borg and Gall, which includes three main stages: content expert validation, module expert validation, and user testing conducted in two ECE institutions with a total of 48 children and six teachers over four months. Data analysis using t-tests and N-Gain calculations revealed a significant improvement in honesty, responsibility, empathy, and cooperation, with an average N-Gain of 0.70 (p < 0.05). The research team evaluated the learning module and confirmed its high feasibility, strong engagement potential, and practical applicability in integrating Maluku's cultural narratives with reflective and participatory learning processes. It is engaging and easy to implement because it effectively integrates Maluku's cultural narratives with reflective and participatory learning activities. Theoretically, this research expands the framework of character education rooted in ethnopedagogy by combining moral-narrative and local cultural approaches. In practice, it provides a concrete foundation for teachers and ECE institutions to adopt similar models, thereby strengthening character education grounded in local wisdom relevant to Indonesia's sociocultural context and archipelagic regions.